High‐Frequency Oscillations in the Pallidum: A Pathophysiological Biomarker in Parkinson's Disease?. Issue 6 (13th April 2021) - Johnson, Luke A.; Aman, Joshua E.; Yu, Ying; Escobar Sanabria, David; Wang, Jing; Hill, Meghan; Dharnipragada, Rajiv; Patriat, Remi; Fiecas, Mark; Li, Laura; Schrock, Lauren E.; Cooper, Scott E.; et al.
ABSTRACT: Background: Abnormal oscillatory neural activity in the beta‐frequency band (13–35 Hz) is thought to play a role in Parkinson's disease (PD); however, increasing evidence points to alterations in high‐frequency ranges (>100 Hz) also having pathophysiological relevance. Objectives: Studies have found that power in subthalamic nucleus (STN) high‐frequency oscillations is increased with dopaminergic medication and during voluntary movements, implicating these brain rhythms in normal basal ganglia function. The objective of this study was to investigate whether similar signaling occurs in the internal globus pallidus (GPi), a nucleus increasingly used as a target for deep brain stimulation (DBS) for PD. Methods: Spontaneous and movement‐related GPi field potentials were recorded from DBS leads in 5 externalized PD patients on and off dopaminergic medication, as well as from 3 rhesus monkeys before and after the induction of parkinsonism with the neurotoxin 1‐methyl‐4‐phenyl‐1, 2, 3, 6 tetrahydropyridine. Results: In the parkinsonian condition, we identified a prominent oscillatory peak centered at 200–300 Hz that increased during movement. In patients the magnitude of high‐frequency oscillation modulation was negatively correlated with bradykinesia. In monkeys, high‐frequency oscillations were mostly absent in the naive condition but emerged after the neurotoxin 1‐methyl‐4‐phenyl‐1, 2, 3, 6 tetrahydropyridine. In patients, spontaneous high‐frequency oscillations were significantly attenuated on‐medication. Conclusions: Our findings provide evidence in support of the hypothesis that exaggerated, movement‐modulated high‐frequency oscillations in the GPi are pathophysiological features of PD. These findings suggest that the functional role(s) of high‐frequency oscillations may differ between the STN and GPi and motivate additional investigations into their relationship to motor control in normal and diseased states. Abstract : This study provides evidence in support of the hypothesis that exaggerated, movement‐modulated high frequency oscillations in the internal segment of the globus pallidus (GPi) are pathophysiological features of Parkinson's disease. © 2021 International Parkinson and Movement Disorder Society